Pengaruh Media Sosial terhadap Perubahan Pola Komunikasi - Dalimunthe, Maulana Andinata; Djuniardi, Rakhas; Siswanda, Dimas (AHKAM, 2024)
This research aims to find out how social media influences changes in communication patterns. Researchers used descriptive qualitative research methods. The results of this research are that social media has a significant impact on changes in communication patterns in modern society, especially in Indonesia. This phenomenon creates a new paradigm in communication, allowing individuals to engage in global conversations, share experiences, and convey ideas through various media such as images, sound, video, and text. The use of social media among students and students, particularly through platforms such as TikTok, has demonstrated changes in social interaction patterns. While providing a space for creative expression, the use of TikTok also shows potential protection, especially in academic contexts. This raises questions about academic integrity and the impact of the dominant entertainment orientation in social media use. In this context, multimedia visualization also has an important role in online communication. The use of visual elements such as graphics, animation and video can increase understanding, appeal and create an immersive experience. However, unwise use can interfere with understanding, reduce credibility, and increase production costs.